YouTube and the Changing Landscape of Global News Flow - Freeman, Bradley C. (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The advent of digital platforms like YouTube has significantly transformed the global news landscape, challenging the long-standing dominance of Western news agencies. Traditionally, global news dissemination has been controlled by a few major Western outlets, resulting in a skewed representation of non-Western perspectives. This paper explores how YouTube is democratizing global news flow by providing a platform for diverse voices, particularly from non-Western regions. Channels such as Al Jazeera, TRT World, CGTN, and others have gained prominence on YouTube, offering alternative viewpoints that enrich global narratives. The platform's algorithm-driven recommendations and ease of access have enabled these channels to reach wide audiences, often surpassing traditional media in viewership. However, YouTube's content moderation policies and the potential spread of misinformation present challenges that need addressing. Despite these issues, YouTube's role in facilitating real-time reporting, interactive engagement, and niche journalism marks a significant shift in how global news is consumed and produced. This paper argues that while YouTube has its limitations, its potential to transform global news flow by decentralizing control and enhancing the diversity of perspectives is undeniable. Further research is needed to fully understand its impact and to develop strategies for mitigating its challenges.